Inositol pyrophosphates modulate cell cycle independently of alteration in telomere length. (January 2016) - Banfic, Hrvoje; Crljen, Vladiana; Lukinovic-Skudar, Vesna; Dembitz, Vilma; Lalic, Hrvoje; Bedalov, Antonio; Visnjic, Dora
Abstract: Synthesis of inositol pyrophosphates through activation of Kcs1 plays an important role in the signalling response required for cell cycle progression after mating pheromone arrest. Overexpression of Kcs1 doubled the level of inositol pyrophosphates when compared to wild type cells and 30 min following the release from α-factor block further increase in inositol pyrophosphates was observed, which resulted that cells overexpressing Kcs1 reached G2 /M phase earlier than wild type cells. Similar effect was observed in ipk1Δ cells, which are unable to synthesize IP6 -derived inositol pyrophosphates (IP7 and IP8 ) but will synthesize IP5 -derived inositol pyrophosphates (PP-IP4 and (PP)2 -IP3 ). Although ipk1Δ cells have shorter telomeres than wild type cells, overexpression of Kcs1 in both strains have similar effect on cell cycle progression. As it is known that PP-IP4 regulates telomere length through Tel1, inositol polyphosphates, cell cycle and telomere length were determined in tel1Δ cells. The release of the cells from α-factor block and overexpression of Kcs1 in tel1Δ cells produced similar effects on inositol pyrophosphates level and cell cycle progression when compared to wild type cells, although tel1Δ cells possesses shorter telomeres than wild type cells. It can be concluded that telomere length does not affect cell cycle progression, since cells with short telomeres ( ipk1Δ and tel1Δ ) progress through cell cycle in a similar manner as wild type cells and that overexpression of Kcs1 in cells with either short or normal telomeres will increase S phase progression without affecting telomere length. Furthermore, IP5 -derived inositol pyrophosphates can compensate for the loss of IP6 -derived inositol pyrophosphates, in modulating S phase progression of the cell cycle.